2014
DOI: 10.1038/nmeth.2848
|View full text |Cite
|
Sign up to set email alerts
|

Efficient multivariate linear mixed model algorithms for genome-wide association studies

Abstract: Multivariate linear mixed models (mvLMMs) are powerful tools for testing SNP associations with multiple correlated phenotypes while controlling for population stratification in genome-wide association studies. We present computationally-efficient algorithms for fitting mvLMMs and computing likelihood ratio tests that improve on existing approximate methods in i) computation speed, ii) power/p value calibration, iii) ability to deal with more than two phenotypes. We illustrate these features on real and simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
911
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 747 publications
(919 citation statements)
references
References 56 publications
8
911
0
Order By: Relevance
“…Following the approach taken in ref. 52, we quantile-normalized each trait to follow a unit variance normal distribution. We used genetic features (SNPs) for a total of 328,517 variants with a MAF of at least 1%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the approach taken in ref. 52, we quantile-normalized each trait to follow a unit variance normal distribution. We used genetic features (SNPs) for a total of 328,517 variants with a MAF of at least 1%.…”
Section: Methodsmentioning
confidence: 99%
“…From a total of 328,515 genetic features (SNPs), we report the 40 most associated features identified by the mixed RF. Among these, 29 loci have previously been confirmed in a large meta-study 51 or have been identified using alternative methods applied to the same data 52 Considered were eQTLs for 300 gene expression traits mapped using the identical methods as considered in Fig. 2.…”
Section: Article Nature Communications | Doi: 101038/ncomms8432mentioning
confidence: 99%
“…There are several multiple-phenotypes analysis methods considering population structure Zhou and Stephens 2014). These methods explicitly model the dependencies of phenotypes to accurately estimate associations between a SNP and phenotypes.…”
Section: Efficiency Of Gammamentioning
confidence: 99%
“…Unfortunately, none of the previously discussed multivariate methods are able to correct for population structure and may cause a significant number of false positive results. Recently, multiple-phenotypes analysis methods have been developed that consider population structure Zhou and Stephens 2014). However, these methods are impractical for cases with large number of phenotypes (.100) since their computational time scales quadratically with the number of phenotypes considered.…”
mentioning
confidence: 99%
“…Genome-Wide Association Study (GWAS), locus sequencing by Next-Generation Sequencing (NGS) and Allele-Specific PCR Using the Illumina Canine HD 173k (BeadChip), 62 dogs were genotyped at the Centre National de Génotypage (CNG; Evry, France) and statistical analyses were performed using Plink software (v1.06-1.07) and GEMMA software (v0.94.1) (Purcell et al 2007;Zhou & Stephens, 2014). Locus sequencing was performed by capture-sequencing on four affected and four unaffected dogs by Integragen (Evry, France): the genomic libraries were made using the Illumina paired-end library sample preparation kit (Illumina Inc.), the capture experiment was performed with the Agilent SureSelect Target Enrichment System Kit and samples were paired-end sequenced on an Illumina HiSeq2000.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%